In Situ Small‐Angle X‐ray Scattering Investigation of the Formation of Dual‐Mesoporous Materials. Issue 17 (2nd October 2015) - Schmitt, Julien; Canilho, Nadia; Impéror‐Clerc, Marianne; Blin, Jean‐Luc; Pedersen, Jan Skov; Pérez, Javier; Lebeau, Bénédicte; Vidal, Loic; Stébé, Marie‐José
Abstract: The formation of a 2D‐hexagonal (p6m) silica‐based hybrid dual‐mesoporous material is investigated in situ by using synchrotron time‐resolved small‐angle X‐ray scattering (SAXS). The material is synthesized from a mixed micellar solution of a nonionic fluorinated surfactant, R F 8 (EO)9 (EO=ethylene oxide) and a nonionic triblock copolymer, P123. Both mesoporous networks, with pore dimensions of 3.3 and 8.5 nm respectively, are observed by nitrogen sorption, transmission electron microscopy (TEM), and SAXS. The in situ SAXS experiments reveal that mesophase formation occurs in two steps. First the nucleation and growth of a primary 2D‐hexagonal network (N1), associated with mixed micelles containing P123, then subsequent formation of a second network (N2), associated with micelles of pure R F 8 (EO)9 . The data obtained from SAXS and TEM suggest that the N1 network is used as a nucleation center for the formation of the N2 network, which would result in the formation of a grain with two mesopore sizes. Understanding the mechanism of the formation of such materials is an important step towards the synthesis of more‐complex materials by fine tuning the porosity. Abstract : Twice as good : A dual‐mesoporous material can be synthesized from a mixed micellar solution constituted by a nonionic fluorinated surfactant, R F 8 (EO)9 (EO=ethylene oxide), and a nonionic triblock copolymer, P123. The kinetics of the formation is studied by in situ small‐angle X‐ray scattering and indicates the formation of highly hierarchically structured mesoporous materials.